PIETY : the heartbeat of reformed theology - Beeke, Joel R., 1952- (Phillipsburg, New Jersey : P&R Publishing, 2015)
Beeke examines the importance of piety in Reformed theology, specifically John Calvin, William Ames, and Gisbertus Voetius. After comparing definitions of pietism, he suggests practical ways to cultivate piety in daily life. --
Piety in reformed theology -- Two forms of pietism -- Means that cultivate piety -- Theology and piety : necessary corollaries.
Includes bibliographical references.
Keywords: Piety; Reformed Church -- Doctrines; Piety; Reformed Church -- Doctrines